Lithuanian Labour Migration to Latvia in the Late 19th and Early 20th Centuries - Mačiulis, Dangiras (Acta humanitarica academiae Saulensis, 2026)
The article examines Lithuanian labour migration to the provinces of Courland and Livonia in the late 19th and early 20th centuries. It discusses the main reasons for migration: surplus labour in rural Lithuania, slow development of local industry, and rapid growth of Latvian industry. It shows that Riga and Liepāja became the most important centres of attraction for Lithuanians due to their developed industry, higher wages, and geographical proximity. The article analyses the Latvian labour market, the structure of industry, and its demand for unskilled and semi-skilled labour. It reveals that Lithuanians worked both in industrial enterprises (especially in the chemical, metal, textile, and food industries) and in agriculture in rural areas of Latvia. The article discusses the working and living conditions of Lithuanians, differences in remuneration, and the importance of qualifications for earnings. It also examines the social relations between Lithuanian migrant workers and local workers, including competition in the labour market and conflicts during strikes. The article concludes that Lithuanian labour migration played an important role in the formation of the Latvian economy and the urban proletariat prior to the First World War.